DESIGN OF AN EFFECTIVE COMMUNICATION MODEL BASED ON MAPPING AUDITOR NEEDS AT THE INSPECTORATE GENERAL KEMENDIKTISAINTEK - Agatha Yerika Septininditya; Nurtanio Agus Purwanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to map the effective communication needs of auditors as a basis for developing a communication model at the Inspectorate General of the Ministry of Higher Education, Science, and Technology. The research approach uses a mixed methods approach with a quantitative and qualitative descriptive design. A total of 20 auditors participated in filling out the questionnaire, and 5 auditors were interviewed to reinforce the quantitative findings. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using thematic analysis to identify patterns of auditors' communication needs and barriers. The results showed that the level of auditors' need for effective communication was very high (mean 4.37). The highest needs were in the aspects of professional communication skills and the ability to convey findings clearly and persuasively. Communication barriers that arose during the audit included ambiguity between message delivery and reception, defensive attitudes from auditees, and the lack of ideal organizational communication guidelines for auditors. Based on auditor preferences, it was also shown that auditors want digital learning media in the form of e-books and e-learning. This is because both e-books and e-learning are considered more flexible and easily accessible by auditors anytime and anywhere. Based on these findings, this study concludes that there is a need to develop a communication model.